1993
DOI: 10.1159/000110326
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Neuropathy in Taiwan: An Etiologic Survey

Abstract: From July 1988 to June 1989, the etiology was registered of 520 patients with generalized neuropathy in 5 neurological centers in Taiwan. The neuropathy was diabetic in 256 cases (49.23%), alcoholic in 45 (8.65%), inflammatory in 34 (6.53%; including 21 with acute inflammatory demyelinating polyneuropathy, 12 with chronic inflammatory demyelinating polyneuropathy, and 1 with chronic relapsing polyneuropathy), 12 with associated malignancy (2.31%), 9 with dysproteinemia (1.73%), uremic in 22 (4.23%), hereditary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 6 publications
2
10
2
5
Order By: Relevance
“…16 In Lin et al series, out of 520 patients inflammatory cause was found in 34 (6.53%) including 21 (4.04%) with acute inflammatory demyelinating polyneuropathy and 12 (2.31%) with chronic inflammatory demyelinating polyneuropathy, and 1 with chronic relapsing polyneuropathy. Renal failure was found in 6.7% cases of our series, which was described in (4.23%) cases of large series of Lin et al 14 Charcot-MarieTooth disease is the most common hereditary neuropathy, affecting 1 of 2,500 people, 4 in our series 6.7% of our cases was diagnosed as Charcot-Marry-Tooth disease (CMTD), 75% and 25% of all CMTD patients were demyelinating and axonal type respectively, all of them had motor defect. In our series 3.3% patients were diagnosed case of SLE, all were sensory type and axonal defect.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…16 In Lin et al series, out of 520 patients inflammatory cause was found in 34 (6.53%) including 21 (4.04%) with acute inflammatory demyelinating polyneuropathy and 12 (2.31%) with chronic inflammatory demyelinating polyneuropathy, and 1 with chronic relapsing polyneuropathy. Renal failure was found in 6.7% cases of our series, which was described in (4.23%) cases of large series of Lin et al 14 Charcot-MarieTooth disease is the most common hereditary neuropathy, affecting 1 of 2,500 people, 4 in our series 6.7% of our cases was diagnosed as Charcot-Marry-Tooth disease (CMTD), 75% and 25% of all CMTD patients were demyelinating and axonal type respectively, all of them had motor defect. In our series 3.3% patients were diagnosed case of SLE, all were sensory type and axonal defect.…”
Section: Resultssupporting
confidence: 55%
“…14,12 In current studies 10% cases were of unknown etiology. Among the idiopathic cases 33% had demyelating, 17% axonal and 50% had mixed type defect.…”
Section: Resultsmentioning
confidence: 51%
“…В основном это были мужчины на 4-м десяти-летии жизни. Среди основных причин выявлены СГБ, сахарный диабет и ХВДП [52][53][54].…”
Section: '2015unclassified
“…Воспалительные полиневро-патии были диагностированы в 34 случаях (6,53 %), в том числе у 21 пациента с СГБ и 13 пациентов с ХВДП [52].…”
Section: '2015unclassified
“…In neurologic series, the prevalence of hypothyroidism as a cause of polyneuropathy is reported to be around 2-4% (3,4). Alterations in peripheral nerves are well documented in myxedema (2), but few data are available in subclinical hypothyroidism (SH) (5).…”
Section: Introductionmentioning
confidence: 99%